Shear bond strength of orthodontic brackets to fluorosed enamel - Mendes, Mónica (2014)
Objectives: To evaluate the influence of dental fluorosis and etching time on the shear bondstrengths (SBSs) of orthodontic brackets to human enamel.Methods: A total of 48 human maxillary central incisors, extracted for periodontal reasonswere used. The sample was divided into three experimental groups (n = 16): group H30 withhealthy teeth and group F30 and F60 with fluorosed teeth (Thylstrup and Fejerskov Indexscores 3–4). After etching the dental enamel with 35% phosphoric acid for 30 s (groups H30and F30) or for 60 s (group F60), metal orthodontic brackets were bonded with TransbondXT adhesive system and light cured (1200 mW/cm2for 10 s). The specimens were thenthermocycled (5–55◦C, 500 cycles), stored in distilled water (37◦C/7 days), and tested inshear (Instron, 1KN, 1 mm/min). Failure mode was classified, with a stereomicroscope (20×magnification), according to the adhesive remnant index (ARI). SBS data were statisticallyanalyzed with 1-way ANOVA, followed by Tukey post hoc tests (˛a= 0.05). Kruskal–Wallis andMann–Whitney nonparametric tests were used to analyze failure data (˛a= 0.05).Results: No statistically significant (p = 0.763) differences were found between F30 and F60,but these groups showed a statistically (p < 0.05) lower bond strength values than H30. Thenon-fluorosed group showed a significantly (p < 0.05) higher ARI score than the other groups.Conclusion: Orthodontic brackets adhesion to enamel is negatively influenced by dental fluo-rosis. Doubling the etching time in fluorosed teeth was not enough to produce similar resultsto those observed in the healthy ones.